Tuberculosis Treatment with DOTS Strategy on Mandiri Practice Doctor as Public Private Mix a Case Study in Kebumen Regency - Arif Komedi; Hari Kusnanto J; Wahyudi Istiono (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Background: Tuberculosis or TB is still a public health problem that poses a global challenge. The spread of this disease through droplets of people who have been infected with tuberculosis bacilli. The incidence of TB transmission is around 5-15%. The TB Control Program in a national strategy is directed toward universal access to quality TB services, this can be achieved by involving all health-care facilities. Public-Private Mix / PPM (the collaboration between government services and private services) is the inclusion of all health service facilities in an effort to expand TB services and TB program continuity with a comprehensive approach. Uncomplicated management of pulmonary tuberculosis must be resolved by doctors who work in health centers/clinics from starting to make clinical diagnoses to managing the disease independently and thoroughly.Objectives: This research is to find out the implementation, obstacles to the implementation of DOTS strategy TB treatment at an independent practice physician in Kebumen Regency, and the form of a collaborative pattern of DOTS strategy TB treatment between independent practice doctors and health centers as a form of collaboration in Public-Private Mix.Methods: This research is a case study with a qualitative descriptive approach. Samples were taken by purposive sampling from puskesmas and health department. The total sample of 25 respondents consisted of 4 independent practice doctors, and from the puskesmas consisted of 5 puskesmas heads, 5 TB officers, 5 TB management officers, 3 Health Office officials, and 3 TB patients. Results: Most independent doctors diagnose based on clinical symptoms of TB and a small portion supported by chest X-ray. All puskesmas have implemented TB management with the DOTS strategy, but the results of TB program achievements are still low. This is because the number of suspected TBs is still low. Puskesmas need networks to find TB suspects. One solution is to form a collaboration scheme between puskesmas and independent practice doctors to improve TB management.Conclusion: The mapping of the implementation and barriers of TB DOTS and the solution to the scheme are in the form of collaboration between puskesmas and independent doctors in the form of PPM (Public Private Mix).